Prolonged Cryopreservation Negatively Affects Embryo Transfer Outcomes Following the Elective Freeze-All Strategy: A Multicenter Retrospective Study - Zhang, Xudong; Wu, Shanshan; Hao, Guimin; Wu, Xueqing; Ren, Haiqin; Zhang, Yinfeng; Yang, Aimin; Bi, Xingyu; Bai, Lina; Zhang, Yunshan; Tan, Jichun (Frontiers in Endocrinology, 2021)
Background: With the development of embryo freezing and warming technology, frozen-thawed embryo transfer (FET) has been widely utilized. However, studies investigating the association between cryopreservation duration and FET outcomes are limited and controversial, and previous studies did not conduct stratification analyses based on demographic or clinical characteristics. Methods: This multicenter retrospective study included 17,826 women who underwent their first FET following the freeze-all strategy during the period from January 2014 to December 2018. Duration of cryopreservation was categorized into five groups: 3–8 weeks, 8–12 weeks, 12–26 weeks, 26–52 weeks, and >52 weeks. Modified Poisson regression and multivariate logistic regression were used to assess the association between cryostorage time of vitrified embryos and transfer outcomes. Moreover, further stratification analyses were performed according to variables with p <0.05 in multivariate models. Results: In this large multicenter study, we observed that storage duration was inversely associated with the possibility of pregnancy and live birth (p <0.001), but not with the risk of ectopic pregnancy and miscarriage. Stratification analyses based on maternal age, the number of oocytes retrieved, and condition of embryo transferred indicated that the inverse correlation was significant in the subpopulation with characteristics: (1) less than 40 years old, (2) more than 3 oocytes retrieved, and (3) only high-quality blastocysts transferred. Conclusion: The results of this large, multicenter, retrospective study suggested that prolonged cryopreservation was inversely associated with the probability of pregnancy and live birth. Therefore, for patients who adopt a freeze-all strategy, early FET might achieve a better outcome.